The Husband’s Inability to Provide A Livelihood as An Excuse For Divorce Perspective Hanafi School and Syafi’i School - Taqiuddin, Luthfi (Sakina: Journal of Family Studies, 2021)
Imam Abu Hanifah and Imam Syafi’i are two salaf scholars who are very influential in the world of Islamic fiqh so that they become the madzhab or basis for Muslims to living life in the world. Interestingly, these two schools of thought have the most striking differences regarding various fiqh problems that arise in society. Likewise, the problem of the husband’s inability to provide a livelihood as an excuse for divorce. The objective of this research are, to identify the concept of livelihood in the perspective of Hanafi School and Syafi’i School and to identify the differences of the Hanafi School and Syafi’i School regarding the husband’s inability to provide livelihood as an excuse for divorce. The type of this research is library research by using a comparative approach. Hanafi school argued, the husband is obliged to provide sufficient levels of the wife’s needs in accordance with the prevailing tradition and this varies along with differences in place, period, and condition. There is no stipulation on the amount of livelihood that a husband must give to his wife because it is not explained in the syari’ah. Furthermore, wives are advised to wait patiently when the husband is unable to provide a livelihood and it is not justified to ask for a divorce because the husband who does not find a way of business that can produce income cannot be burdened in terms of livelihood. Meanwhile, the Syafi’i school has a different view. The Syafi’i school determines the amount of livelihood that a husband must give to his wife, for the rich with two mudd, for those who are middle or intermediate one and a half mudd, and for those who are faqir one mudd. Religion provides provisions for the amount of daily livelihood for the wife, so when the husband does not provide for the wife, then the wife is allowed to sue for divorce from her husband on the grounds that the husband never provides a livelihood.